2022
DOI: 10.1097/ju.0000000000002678
|View full text |Cite
|
Sign up to set email alerts
|

All High-Grade Ta Tumors Should Be Classified as High Risk: Bacillus Calmette-Guérin Response in High-Grade Ta Tumors

Abstract: Purpose: There is variation amongst guidelines with respect to risk stratification of Ta tumors, specifically high-grade (HG) Ta tumors. We sought to investigate the response of all Ta tumors to bacillus Calmette-Gu erin (BCG) and compare response rates based on European Association of Urology (EAU) classification as intermediate-(IR) or high-risk (HR). Materials and Methods: An institutional review of all patients who received adequate BCG from 2000e2018 was conducted. EAU 2021 prognostic risk groups were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
(16 reference statements)
0
6
0
Order By: Relevance
“… 14 Nevertheless, Bree et al concluded that all TaHG tumors should be regarded as high-risk as they confer a significantly higher progression risk (approximately 6% TaHG progress to ≥ T2) than intermediate-risk low-grade Ta when treated with BCG. 15 We believe that in light of this real-world data, TaHG should be always regarded as high-risk due to the substantial 9.2% CSM in the long-term observation.…”
Section: Discussionmentioning
confidence: 81%
“… 14 Nevertheless, Bree et al concluded that all TaHG tumors should be regarded as high-risk as they confer a significantly higher progression risk (approximately 6% TaHG progress to ≥ T2) than intermediate-risk low-grade Ta when treated with BCG. 15 We believe that in light of this real-world data, TaHG should be always regarded as high-risk due to the substantial 9.2% CSM in the long-term observation.…”
Section: Discussionmentioning
confidence: 81%
“…In a retrospective analysis of patients with Ta high-grade UBC long-term risk of disease, progression and recurrence were similar to those with T1 tumors (including low- and high-grade tumors) [ 27 ]. Furthermore, analyzing the risk of disease progression after BCG immunotherapy, Bree et al support consideration of all high-grade UBC as the high-risk group of NMIBC regardless of stage [ 28 ]. Since the application of the WHO 2004/2016 bladder cancer grading system, the proportion of T1 UBC diagnoses documented as low-grade has declined significantly but still varies widely by institution.…”
Section: Discussionmentioning
confidence: 99%
“…Bree et al (page 284) from Houston, Texas and Harrisburg, Pennsylvania examine these issues of risk (intermediate vs high) specifically for those diagnosed with high-grade Ta disease in a timely retrospective review of registry data from a tertiary care referral center. 6 They demonstrate that rates of recurrence, bacillus Calmette-Gu erin (BCG) unresponsive disease and progression were similar despite being differentiated into European Association of Urology intermediate or high risk. The authors conclude that all high-grade Ta tumors have inferior response to adequate BCG (and increased progression) compared to intermediate-risk low-grade tumors.…”
Section: Rethinking Bladder Cancer Risk Categoriesmentioning
confidence: 99%